Capacitance-based liquid holdup measurement of cryogenic two-phase flow in a nearly-horizontal tube. (June 2017) - Chen, Jianye; Wang, Yuchen; Zhang, Wei; Qiu, Limin; Zhang, Xiaobin
Highlights: A Capacitance sensor is designed for liquid holdup measurement of cryogenic fluids. Calibration is conducted with four flow patterns through image method. A liquid holdup-capacitance correlation is proposed. Abstract: Liquid holdup measurement of cryogenic fluids is an area of considerable significance because of its inevitable occurrence in LNG transportation, rocket propellant delivery and superconducting equipment cooling, etc. To measure the liquid holdup of cryogenic two-phase flow, a capacitance sensor was carefully designed, which consists of a pair of optimized concave-electrode form with the electric circuit for the small capacitance detection. Four flow patterns were realized to evaluate the performance of the sensor in visualization experiments with liquid nitrogen and vaporous nitrogen. An image method was employed to calibrate the capacitance sensor, which led to a mathematical relationship between the capacitance and the liquid holdup. The results indicated that the obtained correlation between liquid holdup and capacitance satisfactorily coincided with the measured data.